Evaluation of Simulation-based Training in Airway Management among Maiden Workshop Participants in Enugu, Nigeria: A Mixed-method Study - Nwosu ADG; Ossai EN; Amucheazi AO; Onyekwulu FA; Achi J; Ilo DI (Ibom Medical Journal)
Context: Simulation-based training is a growing format in healthcare education in Nigeria. So far, most evaluation of the outcome have been limited to the usual pre- and post- tests of knowledge acquisition.